Modeling of Corrosion Rate and Resistivity of Steel Reinforcement of Calcium Aluminate Cement Mortar - Cristina Argiz; Miguel Ángel Sanjuán; Pedro Castro Borges; Emiliano Álvarez (Advances in Civil Engineering)
Calcium aluminate cement (CAC) is a binder whose hydrated compounds change over time from cubic phases to hexagonal phases, producing an increase of porosity in reinforced concretes. Thereby, chloride ions, among other steel corrosion promoters, can enter the concrete more easily leading to an increase of the reinforcement corrosion process. When such a transformation of phases is completed, a characteristic value regarding both corrosion intensity (Icorr) and resistivity (related to the ohmic drop of the cementitious material) is reached, which depends mainly on the mix proportions of the material and the curing procedure. This paper presents the characteristic corrosion intensity values of steel embedded in mortars made of CAC after five years of exposure to either a 0.5 mol/l or 1.5 mol/l NaCl solution in order to be applied to estimate the service life of reinforced concrete made of calcium aluminate cement (CAC) which is used in real construction structures. Ohmic drop measurements are also presented to support the values obtained. The aim of this paper is to model the corrosion rate and resistivity of the steel reinforcement of calcium aluminate cement mortar with regard to environmental factors (temperature and chloride content) and mortar quality (water/cement ratio).